The Experimental Study on Anti-bacterial Potency of Coptidis rhizoma extract compare with quantity on Staphylococcus epidermidis - Hyeong-Sik,Seo (Korean Pharmacopuncture Institute, 2007)
Objective : This experimental study was performed to investigate the effect of Coptidis rhizoma extract compared with quantity on Staphylococcus epidermidis that induce keratitis. Methods : MIC was measured by dropping to 50 according to density Coptidis rhizoma extract(100%, 10%, 1%, 0.1%) compared with quantity(40g, 80g, 160g). Anti-bacterial potency was measured by the size of inhibition zone with change of volume. Results : 1. MIC on Staphylococcus epidermidis in Coptidis rhizoma extract was showed anti-bacterial potency compared with quantity and density in 100% and 10% of all samples(40g, 80g, 160g). 2. MIC on Staphylococcus epidermidis in Coptidis rhizoma extract(40g, 80g, 160g) was showed anti-bacterial potency compared with quantity all samples in 100% density, but anti-bacterial potency of 80g, Coptidis rhizoma extract decreased compared with 40g, 3. MIC on Staphylococcus epidermidis in 40g Coptidis rhizoma extract was showed in, of 10% density, 80g Coptidis rhizoma extract was showed in of 10% density, 160g Coptidis rhizoma extract was showed in, of 10% density. Conclusions : Coptidis rhizoma extract was showed anti-bacterial potency compare with quantity and density. In herbal drug, anti-bacterial potency compare with quantity and density must be studied.